2022
DOI: 10.3390/nu14163357
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Hair Follicles from Patients with Female Pattern Hair Loss Are Associated with Nutrient Insufficiency and a Quiescent Metabolic Phenotype

Abstract: Female pattern hair loss (FPHL) is a non-scarring alopecia resulting from the progressive conversion of the terminal (t) scalp hair follicles (HFs) into intermediate/miniaturized (i/m) HFs. Although data supporting nutrient deficiency in FPHL HFs are lacking, therapeutic strategies are often associated with nutritional supplementation. Here, we show by metabolic analysis that selected nutrients important for hair growth such as essential amino acids and vitamins are indeed decreased in affected iHFs compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Nutrient deficiencies associated with FPHL have been increasingly implicated in recent studies, in which the nutritional/metabolite profile of hair follicles may vary from one patient to another, likely due to differences in dietary, hormones, and genetic background. A low abundance of TCA cycle products, including citric, malic acid and lactate, from aerobic glycolysis were found in occipital or parietal intermediate hair follicles in some patients, whereas L-glutamine was increased in other patients [19]. These findings show that FPHL women may differ in the metabolism of nutrients compared with women without the disease, but whether this result can be confirmed through genetic correlation studies remains to be seen.…”
Section: Correlation Between Nutrition and Fphlmentioning
confidence: 83%
See 1 more Smart Citation
“…Nutrient deficiencies associated with FPHL have been increasingly implicated in recent studies, in which the nutritional/metabolite profile of hair follicles may vary from one patient to another, likely due to differences in dietary, hormones, and genetic background. A low abundance of TCA cycle products, including citric, malic acid and lactate, from aerobic glycolysis were found in occipital or parietal intermediate hair follicles in some patients, whereas L-glutamine was increased in other patients [19]. These findings show that FPHL women may differ in the metabolism of nutrients compared with women without the disease, but whether this result can be confirmed through genetic correlation studies remains to be seen.…”
Section: Correlation Between Nutrition and Fphlmentioning
confidence: 83%
“…Despite the fact that data supporting the relationship between hair follicle turnover and nutritional deficiencies in FPHL patients are still lacking, many aspects of FPHL treatment are related to nutritional supplementation. A recent study by Piccini [19] clarified that affected intermediate/miniaturized hair follicles in FPHL display relative nutritional deficiency and dormant metabolism, but the function of absorbing nutrients is not impaired, thus suggesting the potential of nutritional supplementation as an adjunctive therapy for FPHL.…”
Section: Correlation Between Nutrition and Fphlmentioning
confidence: 99%
“…This nding is further supported by the upregulation of the key enzyme ARG1 in balding hair follicles. Additionally, previous research has demonstrated the ability of hair follicles in female pattern hair loss (FPHL) to uptake nutrients such as glutamic acid and cystine 23 . However, our research reveals a notable decrease in arginine uptake in HFs obtained from the balding scalp of patients with AGA.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as waist circumference and blood pressure may play a signi cant role in the development of female AGA 22 . In addition, a relative nutrient insu ciency and dormant metabolism in intermediate HFs of female pattern hair loss has been reported 23 . Hence, the aforementioned studies indicate that there may be changes in the metabolic status of individuals with AGA, and these alterations could potentially be linked to the development and progression of AGA.…”
Section: Introductionmentioning
confidence: 99%
“…1C, D and Tables SI and SII ). Intermediate HFs are overall shorter, and display smaller hair shaft, bulb, and dermal papilla diameter, and thus represent a T→V transition stage that precedes complete HF miniaturization ( 4 , 13 ). Inversely, this was accompanied by a significant increase in the number of T HFs ( p < 0.05) in MXL- or PPR-treated xenotransplants compared with vehicle or non-activated PRP ( Fig.…”
Section: Methodsmentioning
confidence: 99%